(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The development of cosmetics industry over the last few decades was immense, the perception of people towards cosmetics has also changed. Undoubtedly people have started seeing cosmetics as more than luxury product to as a necessity product in the coming days. This article intends to study the transformation of cosmetics industry in the current scenario, based upon utilitarian and hedonic needs. The route that leads to Herbal cosmetics are the disadvantages that were seen by chemical cosmetics over a few years, thus through this article researchers aim to understand the emergence of the Herbal cosmetics over chemical cosmetics. Finally the customers perception towards Herbal cosmetics is tested through various statistical analysis & techniques.